Post-harvest conservation of 'Shelly' and 'Omer' mangoes under refrigerated conditions cultivated in the sub-middle of the São Francisco Valley (Research, Society and Development, 2023)
Mango is one of the most important fruits in the world, but its high perishability after harvest limits its commercialization over long distances. Brazil stands out in world production and exports, showing an increasing potential for growth, either with the search for new cultivars or with the advance in the maintenance of fruit quality. Thus, the objective of this research was to evaluate the post-harvest conservation of Israeli mangoes 'Shelly' and 'Omer' stored under refrigerated conditions. The experiment was conducted at the Agricultural Product Storage Laboratory (LAPA), at the Federal University of São Francisco Valley (UNIVASF). The samples received were sanitized, stored for forty days at a temperature of 12 ºC and evaluated at five-day intervals for differences in absorbance (DA index), skin and pulp color (L*, a* and b*), mass loss (ML), dry matter (DM), firmness and soluble solids (SS). The experimental design was completely randomized in a 2 x 9 factorial scheme (cultivars x storage times), with four replications per treatment, except for DM and ML evaluations. Based on the results, the cultivar Omer responded better to the refrigeration condition for post-harvest conservation than Shelly, showing better performance in the evaluation of parameters of firmness, mass loss, dry matter and colorimetry. 'Shelly' performed better in terms of DA index and soluble solids.